The Influence of Tourist Attraction, Accessibility, and Destination Image on Visitor Satisfaction at The Bogor Botanical Gardens - Fajrijah Febriani; Sinthon Siahaan (LPPM Universitas Asa Indonesia, 2022)
The research was conducted with the aim of finding out the effect of tourist attraction, accessibility, and destination image on visitor satisfaction at the Bogor Botanical Gardens. Quantitative research with primary data is the method used in this study, the researchers distributed questionnaires at the first source to obtain primary data. A total of 100 respondents from visitors to the Bogor Botanical Gardens became the sample in this study which was determined by purposive sampling technique. This research proves that tourist attraction, accessibility, and destination image have a partial influence on visitor satisfaction at the Bogor Botanical Gardens. In this study using multiple linear regression data analysis techniques processed with the IBM SPSS 25 program. In this study it can be seen that tourist attraction has a partial influence on visitor satisfaction with a significant value of 0.000 with a t-count value of 4.744, partial accessibility has the effect on visitor satisfaction with a significant value of 0.000 with a t-count value of 2.666, and the image of the destination partially has an influence on visitor satisfaction with a significance value of 0.010 with a t-count value of 2.626. The variables of tourist attraction, accessibility, and destination image together have a positive and significant influence on visitor satisfaction with a percentage of 55.1%, and a percentage of 44.9% visitor satisfaction at the Bogor Botanical Gardens is influenced by other variables.